Rho Kinase Inhibition Is Essential During In Vitro Neurogenesis and Promotes Phenotypic Rescue of Human Induced Pluripotent Stem Cell‐Derived Neurons With Oligophrenin‐1 Loss of Function. (9th May 2016) - Compagnucci, Claudia; Barresi, Sabina; Petrini, Stefania; Billuart, Pierre; Piccini, Giorgia; Chiurazzi, Pietro; Alfieri, Paolo; Bertini, Enrico; Zanni, Ginevra
Abstract : This study showed the morphological, biochemical, and functional features of human OPHN1‐deficient induced pluripotent stem cells characterized by hyperactive rho kinase (ROCK) signaling and their rescue by treatment with the ROCK inhibitor fasudil. These findings shed light on the relevance of the ROCK pathway during in vitro neuronal differentiation in physiology and disease, not only through morphological changes due to cytoskeletal reorganization but also through epigenetic regulation that allows transcription of genes that are relevant for neuronal differentiation and survival, such as NR4A1 . Abstract : Rho‐GTPases have relevant functions in various aspects of neuronal development, such as differentiation, migration, and synaptogenesis. Loss of function of the oligophrenin‐1 gene ( OPHN1 ) causes X‐linked intellectual disability with cerebellar hypoplasia and leads to hyperactivation of the rho kinase (ROCK) pathway. ROCK mainly acts through phosphorylation of the myosin phosphatase targeting subunit 1, triggering actin‐myosin contractility. We show that during in vitro neurogenesis, ROCK activity decreases from day 10 until terminal differentiation, whereas in OPHN1‐deficient human induced pluripotent stem cells (h‐iPSCs), the levels of ROCK are elevated throughout differentiation. ROCK inhibition favors neuronal‐like appearance of h‐iPSCs, in parallel with transcriptional upregulation of nuclear receptor NR4A1, which is known to induce neurite outgrowth. This study analyzed the morphological, biochemical, and functional features of OPHN1‐deficient h‐iPSCs and their rescue by treatment with the ROCK inhibitor fasudil, shedding light on the relevance of the ROCK pathway during neuronal differentiation and providing a neuronal model for human OPHN1 syndrome and its treatment. Significance: The analysis of the levels of rho kinase (ROCK) activity at different stages of in vitro neurogenesis of human induced pluripotent stem cells reveals that ROCK activity decreases progressively in parallel with the appearance of neuronal‐like morphology and upregulation of nuclear receptor NR4A1 . These results shed light on the role of the ROCK pathway during early stages of human neurogenesis and provide a neuronal stem cell‐based model for the treatment of OPHN1 syndrome and other neurological disorders due to ROCK dysfunction.